Training Teachers to Create Interactive Media Using Canva: Melatih Guru Membuat Media Interaktif Menggunakan Canva (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Interactive learning media are crucial for enhancing elementary education, yet many teachers rely on conventional methods that fail to engage students. Specific Background: Canva, a user-friendly graphic design platform, offers potential for creating effective media, but teachers lack training to utilize it. Knowledge Gap: There is limited focus on integrating technical skills with pedagogical principles in teacher training. Aims: This study aimed to improve teacher competence in creating interactive learning media through Canva training. Results: Training with 24 teachers from SD Muhammadiyah Krian showed an 85% increase in competence, improved creativity, and confidence in using technology. Novelty: The program integrated instructional design principles, combining technical and pedagogical skills. Implications: Practical, technology-based training like this can advance educational quality and support digital transformation in teaching practices.Highlights:• Canva empowers teachers to create engaging and effective interactive learning media.• Training combines technical skills with pedagogical principles for holistic improvement.• Results show significant competence gains, boosting creativity and teaching confidence.Keywords: Canva, Teacher Training, Interactive Media, Digital Education, Elementary Schools